A tailored passive driver for liver MRE in pediatric patients - Lorton, Orane; Toso, Seema; El-Begri Talbi, Hayat; Anooshiravani, Mehrak; Poletti, Pierre-Alexandre; Hanquinet, Sylviane; Salomir, Rares (Frontiers in Pediatrics, 2022)
Objectives Magnetic resonance elastography (MRE) is increasingly used in the pediatric population for diagnosis and staging of liver fibrosis. However, the MR-compatible driver and sequences are usually those used for adult patients. Our feasibility study aimed to adapt the standardized adult MRE passive driver and vibrational parameters to a pediatric population. Methods We designed an elliptic passive driver shaped on a torus equipped with an elastic membrane and adapted to children's morphologies. As a first step, eight children (aged 8–18 years) were enrolled in a prospective pilot study aiming to determine the threshold vibrational amplitude for MRE using a custom passive driver, based on phase aliasing assessment and the occurrence of signal void artifacts on magnitude MR images. In the second step, the practicality and the consistency of the custom driver were assessed in a further 11 pediatric patients (aged 7–18 years). In the third step, we compared our custom driver vs. the commercial driver on six adult volunteers, in terms of the reliable region of interest area within the acquired MRE slices, the shear wave maps’ quality, and measured stiffness values obtained. Results Based on pediatric patient data, the threshold vibrational amplitude expressed as percentage of maximum output was found to be 0.4 and 1.1 times the body weight (kg) at 40 and 60 Hz frequencies, respectively. In comparison to the commercial passive driver, the custom driver improved threefold the contact with the body surface, also enabling a more comfortable examination as self-assessed by the volunteers. Conclusions Our custom driver was more comfortable for the volunteers and was able to generate more homogenous shear waves, yielding larger usable hepatic area, and more reliable stiffness values.